Perancangan Sistem Produksi, Persediaan, dan Pembelian PT. Maju Jaya Mulya - Stephanie Surja; Lius Steven Sanjaya (Bina Nusantara University, 2014)
Analysis and design of information system in PT. Maju Jaya Mulya is aimed to identify the organization needs in controlling and managing the data and information of operational transaction. They will be used as a base for developing a new integrated system that can meet company needs and to face the rivalry from the competitors. The activity in analysis and design is focused in production, inventory management and purchasing activities, as the main business of the company. The analysis and design of the company’s needs will be documented by using unified modeling language. With this information system, there is an expectation that this system will ease the company in doing their activity in production, inventory management and purchasing. This system will also minimize the data lost and human error, which is usually caused by the manual process and storage data of transactional data.